2001
DOI: 10.1094/phyto.2001.91.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Integrated Control of Sclerotinia sclerotiorum in Glasshouse Lettuce Using Coniothyrium minitans and Reduced Fungicide Application

Abstract: All pesticides used in United Kingdom glasshouse lettuce production (six fungicides, four insecticides, and one herbicide) were evaluated for their effects on Coniothyrium minitans mycelial growth and spore germination in vitro agar plate tests. Only the fungicides had a significant effect with all three strains of C. minitans tested, being highly sensitive to iprodione (50% effective concentration [EC50] 7 to 18 μg a.i. ml-1), moderately sensitive to thiram (EC50 52 to 106 μg a.i. ml-1), but less sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 49 publications
1
41
0
2
Order By: Relevance
“…This was followed by rinsing individual sclerotia twice for 1 min in 2 ml SDW in separate wells of a 25 well Petri dish (Bibby Sterilin, Stone). Washing the sclerotia individually eliminated possible cross contamination of sclerotia by a heavily infected sclerotium that could occur during batch washing of sclerotia (Budge & Whipps 2001). The sclerotia were bisected and placed on pairs of agar discs (15 mm diam) in a Petri dish.…”
Section: Coniothyrium Minitans Sclerotial Parasitismmentioning
confidence: 99%
“…This was followed by rinsing individual sclerotia twice for 1 min in 2 ml SDW in separate wells of a 25 well Petri dish (Bibby Sterilin, Stone). Washing the sclerotia individually eliminated possible cross contamination of sclerotia by a heavily infected sclerotium that could occur during batch washing of sclerotia (Budge & Whipps 2001). The sclerotia were bisected and placed on pairs of agar discs (15 mm diam) in a Petri dish.…”
Section: Coniothyrium Minitans Sclerotial Parasitismmentioning
confidence: 99%
“…There have been abundant reports during the last decade about biological fungicides by solid substrates and optimizing production procedures (Pascual et al 1999;Budge and Whipps 2001;Schuster and Schmoll 2010;Damaso et al 2012;Sargin et al 2013). For instance, Pascual et al (1999) showed the solid biological fungicide containing the fungus Epicoccum nigrum on wheat.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve these problems, it is necessary to develop eco-friendly agricultural materials. For biological control, Budge and Whipps (2001) and Whipps and Gerlagh (1992) reported control of sclerotium disease with an antagonistic microbe, but there has been little progress in control with plant originated extracts.…”
Section: Resultsmentioning
confidence: 99%